Bone age estimation using epiphyseal fusion of tibia & fibula and lower end of femur in females - Chaterjee, A; Tyagi, Y; Kumar, M (Journal of Indian Academy of Forensic Medicine, 2021)
through childhood, puberty, and finishes growth as a young adult, the bones of the skeleton change in size and shape. Long bone  growth takes place at the epiphyseal or growth plate, located between the metaphysis and epiphysis. Age estimation is an important  medical examination in civil and criminal cases, where there are no documents available to certify the age, especially in developing  countries like India. There are various methods for age estimations, like dental examination, general physical examination X ray  examination of various bones etc. X ray examination of bones especially for ossification and the union of epiphyses give relatively  reliable results. In criminal cases involving minors as per POCSO Act,age of sexual assault victim is also crucial as different clause  applies for minors. Courts totally depend on medical report for age provided by board of doctors. It is therefore a huge responsibility  on the doctors to be accurate with least degree of error. Keeping accuracy in the mind the present study was undertaken. 100 females  between 10 to 21 were X-rayed and divided in 4 categories (Degree 0- Degree 3) depending on the status of fusion of long bones. 100  % female showed complete fusion at distal end of femur at the age group of 15-16, Proximal end of tibia at the age group of 16-17,  proximal end of fibula at the age group of 15-16, distal end of tibia at the age group of 14-15 and distal end of fibula at the age group  of 14-15.
Keywords: Epiphyseal fusion; Femur; Tibia; Fibula; Age estimation